2023
DOI: 10.1007/s11250-023-03465-y
|View full text |Cite
|
Sign up to set email alerts
|

Farmers’ perceptions and acceptance of crossbred guinea pigs in Mantaro Valley, Peru

Abstract: This study aimed at assessing farmers’ perceptions and acceptance of the proposed breeding strategy of Instituto Veterinario de Investigaciones Tropicales y de Altura (IVITA), located in the Central Andes of Peru. A total of 34 farmers, who had received guinea pigs from IVITA, were interviewed. The questionnaire was performed in Spanish language and covered topics about the guinea pig production, feeding, mating system, training, the main products, perception and acceptance of crossbred lines (“cuy RG”), and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
(14 reference statements)
0
0
0
Order By: Relevance
“…In these respects, Abou Khadiga et al (2008) showed that crossing between paternal line males and maternal line females resulted in increased marketing weight and daily weight gain of growing rabbits compared with those of pure lines. Moreover, Alexander (2023) and Cedano-Castro, et al, (2023) concluded that, it may use rabbit paternal line as sire and maternal line as dam, in mating system to achieve the best productive performance for growing rabbits. Results observed significant differences between three genetic groups of growing rabbits in daily feed intake during the fattening stage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In these respects, Abou Khadiga et al (2008) showed that crossing between paternal line males and maternal line females resulted in increased marketing weight and daily weight gain of growing rabbits compared with those of pure lines. Moreover, Alexander (2023) and Cedano-Castro, et al, (2023) concluded that, it may use rabbit paternal line as sire and maternal line as dam, in mating system to achieve the best productive performance for growing rabbits. Results observed significant differences between three genetic groups of growing rabbits in daily feed intake during the fattening stage.…”
Section: Resultsmentioning
confidence: 99%
“…Advantages of rabbits as micro livestock include small body size, short generation intervals, ability to utilize less competitive feeds, rapid growth, possibility for genetic improvement and production of high-quality meat and beneficial by-products (Egbo et al, 2001;Herbert, 2011). These advantages make rabbits seems to be a great way to solve the shortage in animal protein all over the world especially, when we take the right ways to improve its productive and reproductive ability under consideration.…”
Section: Introductionmentioning
confidence: 99%
“…Pali et.al. (2005:98) stated about monitoring and evaluating participation in society is a tool for empowering local communities of poor farmers to improve well-being of his life (Cedano-Castro et al, 2023). Farmer groups are also an important point for implement and translate the concept of farmers' rights into policies, strategies, and worthy programs in a unified whole and inward development operational steps (Djiwandi, 1994).…”
Section: Society Participationmentioning
confidence: 99%
“…El cuy (Cavia porcellus) considerada como una especie propia de los Andes, generalmente se le encuentra en Argentina, Bolivia, Chile, Perú y Ecuador (Castro-Bedriñana & Chirinos-Peinado, 2021). Esta es explotada primordialmente por su carne ya que presenta algunas características peculiares, además, representan una alta importancia gracias a su facilidad de reproducción y crianza (Castro-Cedano, et al, 2023). El cuy, originario de Latinoamérica, es un roedor que se lo encuentra desde los 0 hasta casi los 4500 m.s.n.m.…”
Section: Introductionunclassified